THE ROLE OF THE LATEST TECHNOLOGIES IN THE TRANSLATION INDUSTRY - MUSULMONOVA SHOKHRUZA MUKHTORJON QIZI (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The translation industry has undergone a radical transformation in recent years due to the rapid advancement of technology. This paper examines how modern technologies like Neural Machine Translation (NMT), Computer-Assisted Translation (CAT) tools, and Translation Management Systems (TMS) are reshaping translation practices. While these technologies offer unprecedented efficiency and scalability, they also present challenges regarding quality assurance, ethical considerations, and the evolving role of human translators. The study analyzes current technological trends, their impact on translation workflows, and the emerging hybrid model that combines artificial intelligence with human expertise. Special attention is given to ethical concerns in machine translation, data privacy issues, and the necessary competencies for translators in this new technological landscape.